The Study of Potentials and Problems in Reading Faced By the Eighth Grade Students of Junior High School - Istri Utami, Ida Ayu Made (Journal of Education Reseach and Evaluation, 2017)
Knowing studentsâ problems, especially in reading, is very important to design an appropriate and meaningful learning. From the problem identification, teacher can find the potency of designing and developing material to meet studentsâ need. Therefore, this study was aimed to identify the potentials and problems toward reading lesson faced by the eighth grade students of Junior High School. This study was based on the result of classroom observation, document study, and also checklists. The identification of potency and problems through classroom observation was done to obtain data on how existing reading material was used in teaching reading on the classroom. There was also document study to evaluate existing reading material and syllabus used for teaching reading. Then, the data from the teacher and students had been gathered by administering checklists. From the result of the study, it can be identified that the problems faced by the eighth grade students of Junior High School in reading dealt with topic selection, pictures or illustration, and reading activities, while the potency was to develop new reading material by using those problems as consideration.